Disability Models and Inclusive Education: A Critical Review - Ogaro, Tyrone (Indonesian Journal of Teaching and Learning, 2026)
Purpose – This paper critically examines major theoretical models of disability and their implications for inclusive education, highlighting the historical evolution of how disability has been conceptualized and applied in educational contexts. Methodology – A systematic review design was employed. Relevant scholarly literature was identified, synthesized, and critically analysed to extract key themes, debates, and comparative insights on disability models. The review focused on four dominant frameworks: the medical, social, biopsychosocial, and human rights models. Thematic synthesis was used to interpret patterns across the selected sources and evaluate each model’s relevance to inclusive education. Findings – The review found that each disability model provides valuable perspectives but also contains significant limitations. These frameworks strongly influence inclusive education policies and practices, shaping curriculum design, assessment approaches, teacher training, and accessibility standards. No single model was found to be fully sufficient for addressing the complexity of disability in educational settings. The study concludes that inclusive education requires a more integrated and nuanced understanding of disability, combining strengths across models to better inform policy and practice. Novelty – This study offers a critical and comparative synthesis of disability models specifically in relation to inclusive education, advocating for an integrated approach rather than reliance on a single theoretical framework. Significance – The study benefits policymakers, educators, researchers, and disability advocates by clarifying how disability models shape educational outcomes and by providing guidance for building more effective, truly inclusive educational environments.